Determination of optical constants from Martian analog materials using a spectro-polarimetric technique. (January 2021) - Alemanno, G.; Garcia-Caurel, E.; Carter, J.; Poulet, F.; Brunetto, R.; Alèon-Toppani, A.; Urso, R.G.; Mivumbi, O.; Boukari, C.; Godard, V.; Borondics, F.
Abstract: The technique of spectroscopic ellipsometry is a powerful tool for the characterization of the optical properties of materials. This technique represents a significant refinement over the semi-empirical approach to optical constants determination using BRDF (Bidirectional Reflectance Distribution Function) measurements of a finite set of grain sizes for each mineral. It also allows obtaining, not only the optical constants, but also information about the dependence of optical response on sample orientation respect to the illuminating light beam. In this work, we present our experimental approach to derive optical constants of Martian analogue materials based on an infrared ellipsometry technique. We derived the optical constants of gypsum between 750 and 5000 ​cm −1 (2–13 ​μm) using data obtained with an infrared spectroscopic Mueller ellipsometer. Thanks to the high sensitivity of the ellipsometric measurements, and despite of a rather complex data analysis protocol, the results obtained for the gypsum samples show that it is possible to successfully use this technique for direct determination of optical constants of natural minerals. The method discussed here can provide the planetary science community with laboratory derived optical constants of a large number of minerals and materials (either natural or synthetic). Highlights: Experimental determination of optical constants of Martian analogue materials. Application of an infrared spectroscopic ellipsometry technique. Data modeling by means of Kim oscillators and study of the pseudo-dielectric function. Laboratory derived optical constants of gypsum samples compared with literature.